Partial discharge patterns in high voltage insulation - Illias, Hazlee Azil; Teo, Soon Yuan; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Chen, George; Lewin, Paul L. (2012)
Partial discharge (PD) is an electrical discharge, which does not bridge the electrodes between an insulation system completely under high electric field stress. PD events may affect the performance of insulation system because in long term, it may cause the breakdown of insulation system and failure of high voltage component due to repetition of PD events. In this work, two techniques of analysing PD data have been studied; the phase resolved partial discharge (PRPD) pattern and pulse sequential analysis (PSA) techniques. These two techniques were used to distinguish three main types of PD; they are corona, void and surface discharges. PD data were obtained from the measurement in high voltage laboratory in the University of Southampton, UK. In the end of the analysis, comparison between the PRPD and PSA methods was done to evaluate the advantages and disadvantages between the two techniques.